2020
DOI: 10.7150/ijbs.37275
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α1 promotes tumorigenicity and progressive capacity of colorectal cancer

Abstract: Colorectal cancer (CRC) is the second leading cause of death globally. Integrin α1 (ITGA1) belongs to integrin family and involves in regulating cell adhesion, invasion, proliferation and tumorigenicity, its expression is up-regulated in various cancers, including CRC. However, the molecular understanding and clinical relevance of ITGA1 in the development and progression of CRC remain unclear. In the present study, we detected ITGA1 in 50 CRC tissues and adjacent non-cancerous tissues, sera from 100 CRC patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…ITGA1, also known as CD49a or VLA1, encodes the α subunit of integrin receptors and plays an important role in cell–cell adhesion 25 . ITGA1 was highly expressed in TMZ-resistant pancreatic cancer, and downregulated ITGA1 restored the sensitivity of the above cells to TMZ 26 .…”
Section: Discussionmentioning
confidence: 99%
“…ITGA1, also known as CD49a or VLA1, encodes the α subunit of integrin receptors and plays an important role in cell–cell adhesion 25 . ITGA1 was highly expressed in TMZ-resistant pancreatic cancer, and downregulated ITGA1 restored the sensitivity of the above cells to TMZ 26 .…”
Section: Discussionmentioning
confidence: 99%
“…ITGA1 is highly expressed in pancreatic cancer [ 15 ], colorectal cancer [ 16 , 17 ], and GC [ 18 ]. Another study found that it was significantly related to colon tumor metastasis and clinical staging and can promote the invasion, migration, and tumorigenicity of colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that it was significantly related to colon tumor metastasis and clinical staging and can promote the invasion, migration, and tumorigenicity of colon cancer cells. In vivo and in vitro experiments proved that ITGA1 is an oncogene and may be considered a new target for colon cancer diagnosis and treatment [ 16 , 17 ]. ITGA1 gene is also involved in peritoneal metastasis of GC cells [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, overexpressing KIT led to upregulation of genes involved in ERK, cAMP and WNT signalling (such as LEF1, SOX13, ADCYAP1 and ITGA1 27 ) as well as the HIPPO signalling pathway (TEAD2) (Supplementary Fig. 2c).…”
Section: Re Expressing Cells Display Extensive Differences In Gene Expression and The Active Chromatin Landscape As Compared To Normal CDmentioning
confidence: 99%